CircRNA_103765 acts as a proinflammatory factor via sponging miR-30 family in Crohn’s disease - Yulan Ye (Nature Portfolio, 2021)
Abstract Increasing evidence suggests that circular RNAs (circRNAs) play critical roles in various pathophysiological activities. However, the role of circRNAs in inflammatory bowel disease (IBD) remains unclear. Here we report the potential roles of hsa_circRNA_103765 in regulating cell apoptosis induced by TNF-α in Crohn’s disease (CD). We identify that CircRNA_103765 expression was significantly upregulated in peripheral blood mononuclear cells (PBMCs) of patients with active IBD. A positive correlation with TNF-α significantly enhanced circRNA_103765 expression in CD, which was significantly reversed by anti-TNF-α mAb (infliximab) treatment. In vitro experiments showed that TNF-α could induce the expression of circRNA_103765, which was cell apoptosis dependent, while silencing of circRNA_103765 could protect human intestinal epithelial cells (IECs) from TNF-α-induced apoptosis. In addition, circRNA_103765 acted as a molecular sponge to adsorb the miR-30 family and impair the negative regulation of Delta-like ligand 4 (DLL4). Collectively, CircRNA_103765 is a novel important regulator of the pathogenesis of IBD via sponging miR-30 family-mediated DLL4 expression changes. Blockade of circRNA_103765 could serve as a novel approach for the treatment of IBD patients.